Gagasan Model Pembelajaran Mobile–NOS Untuk Peningkatan Literasi Sains Siswa - Khery, Yusran; Nufida, Baiq Asma; Suryati, Suryati; Rahayu, Sri; Budiasih, Endang (Hydrogen: Jurnal Kependidikan Kimia, 2019)
This article describes the idea of a mobile learning model - NOS for enhancing students' scientific literacy and student responses to these ideas. This article is compiled based on literature studies, simple observations on several variables supporting mobile learning at IKIP Mataram, and evaluating prospective user responses to the development idea using a questionnaire. Respondents were 54 students of IKIP Mataram Chemistry education. The response data is processed by percentage formula based on category criteria. Mobile-NOS learning is learning that applies the Nature of Science (NOS) learning steps with the support of learning media in the form of mobile applications that can be applied in smart mobilephone. The six main steps in implementing learning are oriented to Nature of Science (NOS), namely: (1) Reading the context on electronic articles; (2) Indepth questioning; (3) Observation of cases and targets; (4) Demonstration Procedure; (5) Library Search; (6) Implementing Procedures; (7) Communicating Science Knowledge; and (8) Authentic Assessment.The results of this study showed an average response to the idea of developing NOS-oriented mobile learning at 85.23% with a very good category.